Development of a World Health Organization indicator and corresponding questions to measure effective coverage of rehabilitationResearch in context - Wouter De Groote; Pierre Côté; Jessica J. Wong; Sheilah Hogg-Johnson; Tara Chen; Linamara Battistella; George K.C. Wong; Jan Hartvigsen; Jill A. Hayden; Rajani Mullerpatan; Farooq A. Rathore; Hana Alsobayel; et al. (EClinicalMedicine, 2025)
Summary: Background: Rehabilitation services are essential health services that should be made available to a population. Measuring effective coverage requires the assessment of whether a population's health services needs are met and whether they are met through quality interventions that produce the desired health gain. We propose a global indicator and corresponding questions to measure effective coverage of rehabilitation through population-based surveys. Methods: An indicator to measure effective coverage of rehabilitation requires a clear definition of rehabilitation service need, utilization, and quality. These terms are defined for a tracer health condition with impact on functioning and for which rehabilitation services are beneficial. We selected chronic primary low back pain as the tracer health condition. Following technical input from experts early 2023, we drafted and cognitively tested a set of questions from August till November 2023 to provide key data points for calculating the number of people living with chronic primary low back pain who received rehabilitation services. To determine whether quality rehabilitation services have been delivered, the health gain or benefit can be measured using a valid functioning measure with a known Minimal Important Change value, i.e. a minimal improvement that is meaningful to the client. We selected the shorter version of World Health Organization Disability Assessment Schedule 2.0 to meet this criterion. Findings: The proposed global indicator is defined as the proportion of adults with chronic primary LBP experiencing limitations in functioning that benefited from rehabilitation. There are eight corresponding questions to calculate the number of adults with chronic primary LBP experiencing limitations in functioning and utilizing rehabilitation services. The assessment of a benefit of received rehabilitation services is based on a change in functioning that is greater than the Minimal Important Change measured with World Health Organization Disability Assessment Schedule 2.0 12-item (simple scoring). The Minimal Important Change was set at 6 points following a secondary analysis of studies reporting on rehabilitation outcomes for people with chronic low back pain. Interpretation: We propose a global tracer indicator for measuring effective coverage of rehabilitation at the population level that is captured through population-based surveys. This global indicator uses chronic primary low back pain as the tracer health condition and World Health Organization Disability Assessment Schedule 2.0 12-item to assess whether quality interventions have been provided that produce the desired health gain. Funding: This research received no specific grant from any funding agency in the public, commercial or not-for-profit sectors.